Two-year clinical outcome of patients with mildly reduced ejection fraction after acute myocardial infarction: insights from the prospective KAMIR-NIH Registry - Jeon, Ho Sung; Lee, Jun-Won; Moon, Jin Sil; Kang, Dae Ryong; Lee, Jung-Hee; Youn, Young Jin; Ahn, Min-Soo; Ahn, Sung Gyun; Yoo, Byung-Su (Frontiers in Cardiovascular Medicine, 2024)
Background Left ventricular ejection fraction (LVEF) is a crucial prognostic indicator of acute myocardial infarction (AMI). However, there is a lack of studies on the clinical characteristics and prognosis of patients with mildly reduced ejection fraction (EF) after AMI. Methods We categorized 6,553 patients with AMI from the Korea Acute Myocardial Infarction Registry-National Institutes of Health (KAMIR-NIH) between November 2011 and December 2015 into three groups based on their EF, as assessed by echocardiography during index hospitalization: reduced EF (LVEF ≤40%), mildly reduced EF (LVEF 41%–49%), and preserved EF (LVEF ≥50%). The primary outcome was all-cause death within 2 years. The secondary outcomes included myocardial infarction (MI), revascularization, and patient-oriented composite endpoint (POCE), which was defined as a composite of all-cause death, any MI, or revascularization. Results Of the total 6,553 patients, 884 (13.5%) were classified into the reduced EF group, 1,749 (26.7%) into the mildly reduced EF group, and 3,920 (59.8%) into the preserved EF group. Patients with mildly reduced EF exhibited intermediate mortality (reduced EF, 24.7%; mildly reduced EF, 8.3%; preserved EF, 4.6%; p < 0.0001), MI (3.9% vs. 2.7% vs. 2.6%; p < 0.0046), and POCE (33.0% vs. 15.6% vs. 12.4%; p < 0.0001) rates, albeit closer to those of the preserved EF. After adjustment for demographics, risk factors, admission status, and discharge medications, patients with mildly reduced EF showed a lower risk of all-cause death than those with reduced EF (mildly reduced EF group as a reference: HR, 1.74; 95% CI, 1.40–2.18; p < 0.001), but it did not differ significantly from those with preserved EF (HR, 0.94; 95% CI, 0.75–1.18; p = 0.999) Conclusions Over a 2-year follow-up period, patients with AMI and mildly reduced EF demonstrated better prognoses than those with reduced EF, but did not differ significantly from those with preserved EF. Clinical Trial Registration cris.nih.go.kr, identifier: KCT−0000863.